Sensitivity of Romberg Test in Diagnosis of Peripheral Vestibular Disorders in Comparison with Caloric Test: Psychometric Study - Fatemeh Moghadasi-Boroujeni; Mansoureh Adel Ghahraman (مجله پژوهش در علوم توانبخشی, 2020)
Introduction: Romberg test is one of the balance screening tests. Since this test does not require special equipment, it is widely used in the evaluation of people suffering from balance disorders. This study aimed to determine the sensitivity of the Romberg test for the diagnosis of peripheral vestibular dysfunction compared with the caloric test that is the gold standard for the diagnosis of horizontal semicircular canal/superior vestibular nerve disorders.Materials and Methods: This study was a cross-sectional-comparative study and the sample was selected from those who referred to the audiology clinic of the School of Rehabilitation Sciences, Tehran University of Medical Sciences, Tehran, Iran. Romberg test with closed eyes was performed in 47 people suffering from unilateral or bilateral peripheral vestibular disorders (25 women and 22 men, mean age: 43.80 ± 4.46 years) whose lesion was confirmed by caloric test. The results were recorded in the participants’ history files and the files were reviewed. Chi-square test was used to compare the results. The sensitivity of Romberg test was determined in comparison with their caloric test results.Results: Only 5 participants had abnormal Romberg results, while 35 patients showed unilateral caloric weakness and 12 had bilateral deficits. Therefore, Romberg's sensitivity was 10.64%. There was no significant correlation between Romberg results and duration of disease.Conclusion: Romberg test seems to have low sensitivity in diagnosis of peripheral vestibular disorders. Therefore, vestibular tests with higher sensitivity are recommended for the diagnostic purposes and caloric test may not be replaced by Romberg test.